Analysis of Factors that Influence the Enterprises Interests of Gorontalo State University Students - Idris Yanto Niode (AIBPM Publisher, 2018)
The purpose of this study is to analyze and find out: 1). partial influence and simultaneous individual factors (personal) partially Sociological (Sociological) and environment (Environmental) towards interest student entrepreneurship from Gorontalo State University. The population of this study was all State University students Gorontalo. The sampling technique is done by purposive method sampling of 98 respondents / students with the criteria of students ever get a student entrepreneurship program grant and ever take part in entrepreneurship courses. Hypothesis testing is done with using multiple linear regression analysis with hypothesis testing using the t-test and F-test (ANOVA). The results of the study obtained the regression model equation is Ŷ = 0.873 + 0.186X 1 + 0.279X 2 + 0.085X 3 + e, Based on the partial test (calculated t test) obtained that that individual (personal), Sociological (Sociological) and environmental factors (Environmental) partially influences the interest in entrepreneurship Gorontalo State University students. ANOVA test (calculated F test) was concluded that individual (personal), Sociological (Sociological) and environmental factors (Environmental) together have an effect on interest entrepreneurship for students at Gorontalo State University. Results regression model this research proved to be correct and feasible to use for forecasting. From the results this test is obtained by the coefficient of determination (R²) or the factor contribution value individuals (personal), Sociological (Sociological) and environment (Environmental) amounting to 0.506 or 50.6% while the remaining 0.494 or 49.4% in the form contributions from other factors not examined such as motivation, knowledge, education, and others. Keywords: individuals (personal), Sociological (Sociological), environment, (Environmental) and Entrepreneurial Interest